Kecerdasan Emosional Dan Berfikir Logis Pengaruhnya Terhadap Hasil Belajar Ekonomi - Maemunah, Maemunah; Herman, Herman; Rahmatullah, Rahmatullah (Universitas Negeri Makassar, 2018)
The Research purpose is 1. How to know the influence of emotional intelegent through study result of student partisipan MAN Wajo and SMAN 5 Wajo. The research type is expost facto research is student parcitipan MAN Wajo and SMAN 5 Wajo in class XI IIS. Sample that used number 122 divided into 60 students participant MAN Wajo and 62 student participant SMAN 5 Wajo. Data collection technique apply with using questionnaire in scale likert shape to know the influence emotional entelegent and logical tehniqque whil study result take from technique report score. Data analysis use descriktive analysis technique. Conditional test ofinfrencial statistic analysis. The result of research show 1. Emotional entelegent is significant influenced economy result of student partisipan of MAN Wajo and SMAN 5 Wajo 2. Logical thinking is significant influenced through economy study result of student psrcitipsn of MAN Wajo and SMAN 5 Wajo. 3. Emotional intelegent and logical thngking is significant influenced together trought economi study result of student participant of MAN Wajo and SMAN 5 Wajo. 4. Double liner analysis result show that as simultant variabel emotion intelegent and logical thingking have is significant influence trought economy study result of students participant MAN Wajo and SMAN 5 Wajo.